Silicon attenuates calcium deficiency by increasing ascorbic acid content, growth and quality of cabbage leaves - da Silva, Dalila Lopes [UNESP]; de Mello Prado, Renato [UNESP]; Tenesaca, Luis Felipe Lata [UNESP]; da Silva, José Lucas Farias [UNESP]; Mattiuz, Ben-Hur [UNESP] (Springer Nature, 2021)
Calcium (Ca) deficiency in cabbage plants induces oxidative damage, hampering growth and decreasing quality, however, it is hypothesized that silicon (Si) added to the nutrient solution may alleviate crop losses. Therefore, this study aims at evaluating whether silicon supplied in the nutrient solution reduces, in fact, the calcium deficiency effects on cabbage plants. In a greenhouse, cabbage plants were grown using nutrient solutions with Ca sufficiency and Ca deficiency (5 mM) without and with added silicon (2.5 mM), arranged as a 2 × 2 factorial in randomized blocks, with five replications. At 91 days after transplanting, the plants were harvested for biological evaluations. In the treatment without added Si, Ca deficiency promoted oxidative stress, low antioxidant content, decreased dry matter, and lower quality leaf. On the other hand, added Si attenuated Ca deficiency in cabbage by decreasing cell extravasation while increasing both ascorbic acid content and fresh and dry matter, providing firmer leaves due to diminished leaf water loss after harvesting. We highlighted the agronomic importance of Si added to the nutrient solution, especially in crops at risk of Ca deficiency.